Robustness of Pullback Attractors for 2D Incompressible Navier-Stokes Equations with Delay (Journal of Partial Differential Equations, 2024)
This paper is concerned with the pullback dynamics and robustness forthe 2D incompressible Navier-Stokes equations with delay on the convective term inbounded domain. Under appropriate assumption on the delay term, we establish theexistence of pullback attractors for the fluid flow model, which is dependent on thepast state. Inspired by the idea in Zelati and Gal’s paper (JMFM, 2015), the robustnessof pullback attractors has been proved via upper semi-continuity in last section.